Information management research and practice in the post-COVID-19 world. (December 2020) - Barnes, Stuart J.
Highlights: Context for research and practice has been permanently transformed. Pandemic rapidly accelerated predicted trends in information management. Unprecedented new opportunities for research to impact practice. Wide-reaching research impacts across human endeavour and global society. Understanding and solutions needed for problems from digitalization. Abstract: COVID-19 has radically transformed many aspects of human life and global society both now and for many years to come. A key aspect of the transformation has been increased digitalization and the accelerated implementation of previously predicted trends that have been discussed for many years in the information management literature. Human endeavour has encouraged us to adapt to the "new normal" through immediate necessity in areas such as work, education, healthcare, entertainment and leisure, and online commerce. This new environment has provided unprecedented opportunities for the information management research community to develop research that will have a significant impact on practice in these and other areas. We are essentially at the pinnacle of new developments in the digital space and must seek to develop exemplars that can help to signpost the future direction of digital global society for the benefit of all. Notwithstanding, the problems of digitalization have also been exacerbated and must be further understood and ameliorated in the post-COVID world. This paper examines opportunities and problems in information management brought about by the COVID-19 pandemic. It details implications for research and practice.